2020
DOI: 10.1021/acs.est.0c04462
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation of Mercury and Its Isotopes in Atmospheric Particles at the Coastal Zhongshan Station, Eastern Antarctica

Abstract: Mercury (Hg) is a globally spread trace metal due to its long atmospheric residence time. Yet, our understanding of atmospheric processes (e.g., redox reactions and deposition) driving Hg cycling is still limited, especially in polar regions. The Antarctic continent, by virtue of its remoteness, is the perfect location to investigate Hg atmospheric processes in the absence of significant local anthropogenic impact. Here, we present the first 2 year record (2016–2017) of total suspended particulate mercury (PHg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 85 publications
2
29
0
Order By: Relevance
“…The fitted slope of Δ 199 Hg/Δ 201 Hg ratios in the austral winter was 0.83 ± 0.11 (mean ± 1SD, R 2 = 0.79, P < 0.01, Figure S3). For reference, two of the most negative Δ 199 Hg values observed in PBM at another coastal station, Zhongshan, the eastern Antarctic (Figure S1), were also observed in March and October . Positive MDF and negative odd-MIF could be observed in most PBM values at the Zhongshan station (Figure ) compared to isotopic compositions of TGM at GWS, and the fitted slopes of Δ 199 Hg/Δ 201 Hg ratios in PBM at the Zhongshan station were 0.77 and 0.65 in the austral autumn and winter, respectively .…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…The fitted slope of Δ 199 Hg/Δ 201 Hg ratios in the austral winter was 0.83 ± 0.11 (mean ± 1SD, R 2 = 0.79, P < 0.01, Figure S3). For reference, two of the most negative Δ 199 Hg values observed in PBM at another coastal station, Zhongshan, the eastern Antarctic (Figure S1), were also observed in March and October . Positive MDF and negative odd-MIF could be observed in most PBM values at the Zhongshan station (Figure ) compared to isotopic compositions of TGM at GWS, and the fitted slopes of Δ 199 Hg/Δ 201 Hg ratios in PBM at the Zhongshan station were 0.77 and 0.65 in the austral autumn and winter, respectively .…”
Section: Resultsmentioning
confidence: 90%
“…For reference, two of the most negative Δ 199 Hg values observed in PBM at another coastal station, Zhongshan, the eastern Antarctic (Figure S1), were also observed in March and October. 61 Positive MDF and negative odd-MIF could be observed in most PBM values at the Zhongshan station (Figure 1) compared to isotopic compositions of TGM at GWS, 61 and the fitted slopes of Δ 199 Hg/Δ 201 Hg ratios in PBM at the Zhongshan station were 0.77 and 0.65 in the austral autumn and winter, respectively. 61 These phenomena may be associated with AMDEs through a mechanism such as the oxidation process at a continental scale.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…These observations revealed that the atmosphere of the Antarctic continent during the sunlit season has a high oxidization capacity that could result in a high GOM content and/or obvious depletion of GEM (Angot, Dastoor et al., 2016). Several studies have shown that the Antarctic Plateau plays a key role in influencing the atmospheric Hg cycle at a continental scale (Angot, Dastoor et al., 2016; Li et al., 2020; Temme et al., 2003).…”
Section: Introductionmentioning
confidence: 99%